Wood cultivated ginseng exerts immunostimulatory activity in mouse macrophages, RAW264.7 cells and anti-obesity activity in mouse adipocytes, 3T3-l1 cells - Na Gyeong Geum (Food and Agricultural Immunology, 2021)
We evaluated in vitro anti-obesity and immunostimulatory activity of wood cultivated ginseng. The roots (WCG-R) and stems (WCG-S) of wood cultivated ginseng reduced the lipid accumulation and TG contents in 3T3-L1 cells. WCG-R and WCG-S inhibited the protein expressions such as CEBPα, PPARγ, perilipin-1, adiponectin and FABP4 related to the lipid accumulation of the mature adipocytes. In addition, WCG-R and WCG-S reduced CEBPα and PPARγ during the differentiation process from preadipocytes to mature adipocytes. WCG-S increased the production of immunostimulatory factors in RAW264.7 cells. TLR2 and TLR4 blocked the production of immunostimulatory factors by WCG-S in RAW264.7 cells. In addition, the inhibition of MAPK and NF-κB signalling pathway reduced WCG-S-mediated production of immunostimulatory factors and the activation of MAPK and NF-κB signalling pathway by WCG-S was suppressed by the inhibition of TLR2/4. These findings indicate that WCG-R and WCG-S may be considered to have anti-obesity and immunostimulatory activity.